2016
DOI: 10.1007/s11356-016-7070-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and estrogenic potential of endocrine disrupting chemicals (EDCs) in estuarine sediments from Mumbai, India

Abstract: Endocrine disrupting chemicals (EDCs) are responsible for inappropriate development and they alter the hormonal and homeostatic systems of organism. Phthalates (PAEs), bisphenol A (BPA) and other EDCs were monitored in surface sediments at different stations across Thane Creek, India. Analysis of PAEs was carried out using GC-MS technique, while BPA and other EDCs were analyzing on UPLC-PDA instrument. Di-n-butyl phthalate (DBP) had the highest concentration among all fourteen analyzed phthalates ranges betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 72 publications
2
5
0
Order By: Relevance
“…The monitoring of EDCs revealed a ubiquitous contamination of sediment samples of the coastal area of Macau with BPA. Detection frequencies of 100% for BPA is similar with frequencies found in other locations in China (Liu et al, 2017;Wang et al, 2016;Zhang et al, 2014) and India (Tiwari et al, 2016). Moreover, the concentration range of BPA in the studied sediments was in the same order of magnitude of that reported for sediments of the Three Gorges Reservoir Region (4.7-41.1 ng g -1 dw) (Wang et al 2016), Songhua River (1.60-17.3 ng g -1 dw) (Zhang et al 2014) and Fen river (Liu et al 2017) and also estuarine sediments from Mumbai, India (16.3-35.79 ng g -1 dw) (Tiwari et al 2016).…”
Section: Monitoring Of Edcs Along the Coastal Areasupporting
confidence: 84%
See 1 more Smart Citation
“…The monitoring of EDCs revealed a ubiquitous contamination of sediment samples of the coastal area of Macau with BPA. Detection frequencies of 100% for BPA is similar with frequencies found in other locations in China (Liu et al, 2017;Wang et al, 2016;Zhang et al, 2014) and India (Tiwari et al, 2016). Moreover, the concentration range of BPA in the studied sediments was in the same order of magnitude of that reported for sediments of the Three Gorges Reservoir Region (4.7-41.1 ng g -1 dw) (Wang et al 2016), Songhua River (1.60-17.3 ng g -1 dw) (Zhang et al 2014) and Fen river (Liu et al 2017) and also estuarine sediments from Mumbai, India (16.3-35.79 ng g -1 dw) (Tiwari et al 2016).…”
Section: Monitoring Of Edcs Along the Coastal Areasupporting
confidence: 84%
“…Detection frequencies of 100% for BPA is similar with frequencies found in other locations in China (Liu et al, 2017;Wang et al, 2016;Zhang et al, 2014) and India (Tiwari et al, 2016). Moreover, the concentration range of BPA in the studied sediments was in the same order of magnitude of that reported for sediments of the Three Gorges Reservoir Region (4.7-41.1 ng g -1 dw) (Wang et al 2016), Songhua River (1.60-17.3 ng g -1 dw) (Zhang et al 2014) and Fen river (Liu et al 2017) and also estuarine sediments from Mumbai, India (16.3-35.79 ng g -1 dw) (Tiwari et al 2016). For the sediments of the Pearl River system previous studies reported values varying from ND-296 ng g -1 dw, with detection frequencies of 83 to 100% in South China (Liuxi River, Zhujiang River and Shijing River) (Zhao et al 2011).…”
Section: Monitoring Of Edcs Along the Coastal Areasupporting
confidence: 84%
“…In addition, concentrations of natural oestrogens (E1, E2 and E3) in the Wulo Creek of southern Taiwan were as high as 1.3 µg l À1 due to the livestock feedlot nearby (Chen et al, 2010). The content of steroid hormones in river and marine sediments is often detected at ng g À1 levels (Huang et al, 2013;Gorga et al, 2015;Praveena et al, 2016;Tiwari et al, 2016).…”
Section: Potential Sources Of Steroid Hormones In Environmentsmentioning
confidence: 99%
“…Consequently, estrogens and others endocrine disruptors chemicals (EDCs) are continuously released into the environment via effluent discharge, resulting in their occurrence in the range of low microgram per liter to few nanogram per liter levels in rivers [ 7 , 8 , 9 ], lakes [ 10 ], sediments [ 8 , 11 ] and even in drinking water reservoirs [ 12 ]. Due to the high concern posed by these contaminants, E2 and EE2 were added to the first EU watch list of emerging substances to be monitored in 2013 (Directive 2013/39/EU).…”
Section: Introductionmentioning
confidence: 99%